Effect of jet injection on infectivity of measles, mumps, and rubella vaccine in a bench model. Issue 36 (26th August 2015) - Coughlin, Melissa M.; Collins, Marcus; Saxon, Gene; Jarrahian, Courtney; Zehrung, Darin; Cappello, Chris; Dhere, Rajeev; Royals, Michael; Papania, Mark; Rota, Paul A.
Abstract: Disposable-syringe jet injectors (DSJIs) with single-use, auto disable, needle-free syringes offer the opportunity to avoid hazards associated with injection using a needle and syringe. Clinical studies have evaluated DSJIs for vaccine delivery, but most studies have focused on inactivated, subunit, or DNA vaccines. Questions have been raised about possible damage to live attenuated viral vaccines by forces generated during the jet injection process. This study examines the effect of jet injection on the integrity of measles, mumps, and rubella vaccine (MMR), measured by viral RNA content and infectivity. Three models of DSJIs were evaluated, each generating a different ejection force. Following jet injection, the RNA content for each of the vaccine components was measured using RT-qPCR immediately after injection and following passage in Vero cells. Jet injection was performed with and without pig skin as a simulation of human skin. There was little to no reduction of RNA content immediately following jet injection with any of the three DSJIs. Samples passaged in Vero cells showed no loss in infectivity of the measles vaccine following jet injection. Mumps vaccine consistently showed increased replication following jet injection. Rubella vaccine showed no loss after jet injection alone but some infectivity loss following injection through pig skin with two of the devices. Overall, these data demonstrated that forces exerted on a live attenuated MMR vaccine did not compromise vaccine infectivity. The bench model and protocol used in this study can be applied to evaluate the impact of jet injection on other live virus vaccines.